Food, memory and transnational gastronomic culture amongst Cameroonian migrants in Cape Town, South Africa. Issue 1 (2nd January 2018) - Nyamnjoh, Henrietta M.
Abstract : In the context of accelerated mobility and migration, food forms part of peoples' historical identity and emotional repertoire. Drawing on ethnographic research amongst Anglophone Cameroonian migrants living in Cape Town, South Africa, this paper explores how Cameroonian migrants maintain their gastronomic culture in Cape Town such that ethnic foods and food parcels mark migrants' identities and socio-cultural lives in the host country. Special occasions like the birth of a child or funerals and memorial services are marked by food preparation and consumption. I argue that food is central to the ways migrants identify themselves both individually and collectively. Migrants' attachment to gastronomic culture suggests that food could be a marker of identity formation and development of the self. This paper contributes to recent literature that considers the role of ethnic food in migrants' everyday lives.